2017
DOI: 10.1111/eci.12728
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte‐bound apolipoprotein B in atherosclerosis and mortality

Abstract: Low ery-apoB is associated with increased mortality and cardiovascular risk, especially in patients with a prior history of CVD. These subjects may benefit from more aggressive secondary prevention treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Interestingly, de Vries et al have shown that binding of apoB-containing lipoproteins to circulating erythrocytes, detected by flow cytometry, is associated with lower cardiovascular mortality. This inverse relationship between atherosclerosis and levels of erythrocyte-apoB binding can be considered as another means to use apoB as a biomarker [ 137 ].…”
Section: Biomarkers For Cvd: Ldl-c and Apobmentioning
confidence: 99%
“…Interestingly, de Vries et al have shown that binding of apoB-containing lipoproteins to circulating erythrocytes, detected by flow cytometry, is associated with lower cardiovascular mortality. This inverse relationship between atherosclerosis and levels of erythrocyte-apoB binding can be considered as another means to use apoB as a biomarker [ 137 ].…”
Section: Biomarkers For Cvd: Ldl-c and Apobmentioning
confidence: 99%
“…More specifically, apolipoprotein B (Apo-B) may be involved in the pathophysiology of AD and CVD; however, there is limited study on this potential involvement [ 30 ]. Atherosclerosis is known to be the most common contributor to CVD, and all the atherogenic lipoproteins have a single Apo-B molecule as their structural protein [ 31 ]. It has been shown that serum Apo-B, as one biomarker, is a strong predictor of CVD [ 32 ] and could play a role in regulating physical function in addition to indirectly impacting the lipid profile [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of their work are, among other things, meant to inform political decision making on science, technology and innovation. As an institute, it was involved in organizing public dialogues on new and existing technologies that (can) have a major impact on society, e.g., nanotechnology (Hanssen et al, 2008), synthetic biology (Rerimassie and Stemerding, 2014) and nuclear waste (De Vries et al, 2015). The ten lessons for the Dutch dialogue on HGGM were based on years of experience, a review of the debate on HGGM in the Netherlands so far and a systematic analysis of the social and ethical issues concerning HGGM.…”
Section: Lessons For a Public Dialoguementioning
confidence: 99%